Review of the Leafhopper Genus Macrosteles Fieber (Hemiptera: Cicadellidae: Deltocephalinae) from China - Zhang, Yalin; Lu, Lin; Yong, Kwon Jung (Zootaxa, 2013)
The leafhopper genus Macrosteles Fieber in China comprises 25 species including ten new species: Macrosteles brochus Zhang & Lu, M. brunneus Zhang & Lu, M. choui Zhang & Lu, M. ehensis Zhang & Lu, M. gracilis Zhang & Lu, M. falcatus Zhang & Lu, M. haperatus Zhang & Lu, M. nabiae Kwon, M. parastriifrons Zhang & Lu and M. spinosus Kwon. Five species are newly recorded from China, including M. abludens Anufriev, M. albicostalis Vilbaste, M. alpinus (Zetterstedt), M. lividus (Edwards) and M. sordidipennis (Stål). One taxon previously treated as a subspecies of M. fascifrons (Stål) is elevated to species rank: M. lindbergi Dlabola, n. stat. The following six new synonyms are proposed: M. bimaculatus Dai, Li & Chen, 2008 = M. lividus (Edwards, 1894), M. heiseles Kuoh, 1981 = M. guttatus (Matsumura, 1915); M. huangxionis Kuoh, 1981 = M. heitiacus Kuoh, 1981; M. latiaedeagus Dai et al., 2008 = M. cristatus Ribaut, 1927; and M. serrata Dai et al., 2011 = M. striifrons Anufriev, 1968 and also a junior homonym of M. serratus Kwon, 2010; and M. symphorosus Yang, 1996 = M. viridigriseus (Edwards, 1924). A checklist to the Macrosteles species from China is provided together with a key for separation of males.